FINANCIAL STATEMENT QUALITY AND INVESTMENT EFFICIENCY - Indah Umiyati; Riyanto Riyanto (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2019)
This study aims to analyze the relationship between financial statements quality with reduced over-investment and under-investment. The study was conducted on companies listed on the Indonesia Stock Exchange in 2008-2015 totaling 1,525 years. The analysis was done using an estimation of multinomial logistic regression. The results of the data analysis show that financial statements quality does not have an influence on the reduced opportunities for over-investment or under investment